STUDY CONCERNING THE SPECTATOR BEHAVIOR ON HANDBALL GAMES - Tudor BOGDAN; Lăcrămioara Cosmina Lazăr; Maria MACRA-OȘORHEAN (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2011)
specialists in recent years. Modern approaches to study the reasons and frequency aspects of the show audienceparticipation sport, the level of affiliation to the team, the aggressive behavior of spectators, most fitting that conductconsumer behavior.Aims - highlighting the structure and behavior of the general features of the audience to play handballSubjects and methods - I applied to a game of handball viewers a non-standardized questionnaire of 15 items, with themajor content themes developed by the literatureResults and discussion - the raw data were processed with Excel and SPSS statistical packages, calculating descriptiveand inferential statistical indices, which were the basis for interpretation of results.Conclusions - The study highlighted a number of features of spectators at games of handball, information analyzedaccording to socio-demographic parameters studied: gender, age, education completed.